The Evil New Woman in Oscar Wilde's Salome and A Woman of No Importance (Journal of the College of Basic Education, 2022)
This research deals with Oscar Wilde's two selected plays, Salome and A Woman of no Importance and, shedding light and concentrating on the author's treatment of woman protagonists in these two plays. Wilde wants to prove that the Victorian period has witnessed the appearance of the new evil woman, the spiteful woman who tries to achieve her goals throughout her sexuality regardless of morals and the common sense. He presents a realistic view of evil woman's existence of the utmost importance to expose that evil is never stop and at last terminate in ruin.